Polarisasi Tahapan Kepemimpinan Transformatif Pendidikan Islam - Doni Nugraha (Program Studi Manajemen Pendidikan Islam, 2023)
The purpose of writing this article is to find out the polarization of leadership stages that are appropriate to be applied in educational institutions. The problem of Indonesian education today is that the quality is not optimal and evenly distributed. The method and type of data collection in this research is library research by collecting books, journals and previous research results that support the research theme, including literature on leadership which includes transformational models, Islamic Education and objective leadership models. The results of this study indicate that the leadership variable is the most important and urgent variable in an effort to create/realize quality education.